Fenomenologia da consciência e ontologia em Sartre - Ecker, Diego (2010)
The objective of this dissertation is to demonstrate the conceptual roots of the phenomenology of consciousness and ontology Sartre characterizes the approach and detachment with the tradition of phenomenology and metaphysics, especially with Husserl and Heidegger emphasizing the relationship and understanding of the concepts themselves and Para- in-itself in the context of existentialist philosophy. Research is carried through the exploration of literature and is divided into three parts. The first was intended to approach the concept of intentionality, travels Husserlian phenomenology, focusing on the constitution of the transcendental ego. The second part aimed to develop a critical overview of phenomenological ontology of Being and Nothingness, often pointing to critical issues regarding the problems of metaphysics and the unilateral conception of realism and idealism. The third part has a contrast of Sartre's phenomenological ontology with the problems resulting from the standoff between the metaphysics of realism and idealism. Finally, we dealt with the problem constructed by putting some problematic aspects of Sartre's phenomenological ontology in view of their involvement with the great questions of Western metaphysics.